IMPLEMENTASI PROGRAM PELATIHAN JABATAN PENGAWAS APARATUR SIPIL NEGARA - Ade Suhendar; Mohammad Fakry Gaffar; Tjutju Yuniarsih; Asep Suryana (Jurnal Al Burhan, 2021)
The purpose of this research is to deeply extrapolate community participation in the fulfillment of educational facilities in elementary schools. The research method used is qualitative method with case study approach. Data collection is done with interviews and documentation studies. This research was conducted at SDN Cicalengka 4 Bandung. The results describe five categories of community participation in the fulfillment of educational facilities, namely facility providers, development supervisors, the role of school committees, labor participation, fund participation. Of the five roles, the role of the school committee will certainly have a big impact in the fulfillment of educational facilities if functioned to the maximum.